Manifestation of Latent Left Ventricular Outflow Tract Obstruction in the Acute Phase of Takotsubo Cardiomyopathy - Ozaki, Kazuyuki (Intern Med, 2016)
Objective Left ventricular outflow tract (LVOT) obstruction is a complication in 15-25% of patients with Takotsubo cardiomyopathy and sometimes leads to catastrophic outcomes, such as cardiogenic shock or cardiac rupture. However, the underlying mechanisms have not been clarified. Methods and Results We experienced 22 cases of Takotsubo cardiomyopathy during 3 years, and 4 of these 22 cases were complicated with LVOT obstruction in the acute phase (mean age 79±5 years, 1 man, 21 women). The LVOT pressure gradient in the acute phase was 100±17 mmHg. Transthoracic echocardiogram (TTE) revealed left ventricular hypertrophy (LVH) in one case and sigmoid-shaped septum without LVH in three cases. The complete resolution of the LVOT obstruction was achieved in a few days with normalization of the left ventricular wall motion following administration of beta-blockers. A dobutamine provocation test after normalization of the left ventricular wall motion reproduced the LVOT obstruction in all cases and revealed the presence of latent LVOT obstruction. Conclusion The manifestation of latent LVOT obstruction in the acute phase of Takotsubo cardiomyopathy is one potential reason for the complication of LVOT obstruction with Takotsubo cardiomyopathy.